Microfluidics-Based Bioassays and Imaging of Plant Cells. (1st July 2021) - Yanagisawa, Naoki; Kozgunova, Elena; Grossmann, Guido; Geitmann, Anja; Higashiyama, Tetsuya
Abstract: Many plant processes occur in the context of and in interaction with a surrounding matrix such as soil (e.g. root growth and root–microbe interactions) or surrounding tissues (e.g. pollen tube growth through the pistil), making it difficult to study them with high-resolution optical microscopy. Over the past decade, microfabrication techniques have been developed to produce experimental systems that allow researchers to examine cell behavior in microstructured environments that mimic geometrical, physical and/or chemical aspects of the natural growth matrices and that cannot be generated using traditional agar plate assays. These microfabricated environments offer considerable design flexibility as well as the transparency required for high-resolution, light-based microscopy. In addition, microfluidic platforms have been used for various types of bioassays, including cellular force assays, chemoattraction assays and electrotropism assays. Here, we review the recent use of microfluidic devices to study plant cells and organs, including plant roots, root hairs, moss protonemata and pollen tubes. The increasing adoption of microfabrication techniques by the plant science community may transform our approaches to investigating how individual plant cells sense and respond to changes in the physical and chemical environment.